2001
DOI: 10.1053/joca.2001.0471
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of Korean Western Ontario and McMaster Universities (WOMAC) and Lequesne Osteoarthritis Indices for Clinical Research

Abstract: The reliability, validity, and responsiveness of the KWOMAC and the KLequesne are confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 13 publications
3
96
0
2
Order By: Relevance
“…Ontario and McMaster Universities Osteoarthritis Index (K-WOMAC), a specific measure assessing pain, stiffness, and physical function in patient with osteoarthritis in the hip or knee [18]. In the current study, the 7 items of the K-WOMAC were selected to measure self-reported joint pain and stiffness.…”
Section: Joint Pain Was Measured Using the Korean Westernmentioning
confidence: 99%
“…Ontario and McMaster Universities Osteoarthritis Index (K-WOMAC), a specific measure assessing pain, stiffness, and physical function in patient with osteoarthritis in the hip or knee [18]. In the current study, the 7 items of the K-WOMAC were selected to measure self-reported joint pain and stiffness.…”
Section: Joint Pain Was Measured Using the Korean Westernmentioning
confidence: 99%
“…AEs after completion of AIF administration were assessed again at seventh week. Pain intensities at weeks 0, 3, and 6 were assessed using a 100 mm visual analogue scale (VAS) by patients, and K-WOMAC scores at weeks 0 and 6 were compared by consensus between two investigators (SH Park, JY Choe) (Bae et al, 2001).…”
Section: Outcome Measures and Assessment Of Efficacymentioning
confidence: 99%
“…The SF-36 is commonly used to represent broad aspects of health for questionnaire validation and reportedly is more responsive than other general health instruments regarding musculoskeletal disorders [6]. The DASH and WOMAC are the most widely used condition-and region-specific instruments to represent QOL related to upper or lower extremity manifestations and are well correlated with general health status measurements such as the SF-36 [4,17]. The DASH is a selfadministered, upper extremity-specific questionnaire and consists of 30 questions: 21 on physical function, five on symptoms, and four on social role functions.…”
Section: Methodsmentioning
confidence: 99%